Providing a Helping Hand: Metabolic Regulation of T Follicular Helper Cells and Their Association With Disease - Mayberry, Colleen L.; Logan, Natalie A.; Wilson, John J.; Chang, Chih-Hao (Frontiers in Immunology, 2022)
T follicular helper (Tfh) cells provide support to B cells upon arrival in the germinal center, and thus are critical for the generation of a robust adaptive immune response. Tfh express specific transcription factors and cellular receptors including Bcl6, CXCR5, PD-1, and ICOS, which are critical for homing and overall function. Generally, the induction of an immune response is tightly regulated. However, deviation during this process can result in harmful autoimmunity or the inability to successfully clear pathogens. Recently, it has been shown that Tfh differentiation, activation, and proliferation may be linked with the cellular metabolic state. In this review we will highlight recent discoveries in Tfh differentiation and explore how these cells contribute to functional immunity in disease, including autoimmune-related disorders, cancer, and of particular emphasis, during infection.